Réponses

2013-10-04T14:00:00+02:00
Salut,
a. Pouur x = - 1
E = 16 - ( 5 * ( - 1 ) - 3 ) ²
= 16 - ( - 5 - 3 ) ²
= 16 - ( - 8 ) ²
= 16 - 64 = - 48
b. Développer
E = 16 - ( 5x - 3 ) ² = 16 - ( 25x² - 2 * 5x * 3 + 9 ) 
= 16 - ( 25x² - 30x + 9 ) = 16 - 25x² + 30x - 9
= - 25x² + 30x + 7
Réduire
E = 16 - ( 5x - 3 ) ²
E = 4 ² - ( 5x - 3 ) ²
E = ( 4 - ( 5x - 3 ) ) * ( 4 + ( 5x - 3 ) )
E = ( 4 - 5x + 3 ) * ( 4 + 5x - 3 )
E = ( - 5x + 7 ) * ( 5x + 1 )
 
Meilleure réponse !
  • Utilisateur Brainly
2013-10-04T14:03:50+02:00
On pose E = 16-(5x-3)²
a) calculer la valeur de E = -1
E=16-(-8)²
E=-48

b) développer et réduire

E = 16-(5x-3)²
   =16-(25x²-30x+9)
   =-25x²+30x+7